Endurance interval training in obese mice reduces muscle inflammation and macrophage content independently of weight loss - Samaan, M. Constantine (Wiley Periodicals, Inc., 2014)
Obesity is associated with chronic low‐grade inflammation that involves infiltration of macrophages into metabolic organs such as skeletal muscle. Exercise enhances skeletal muscle insulin sensitivity independently of weight loss; but its role in regulating muscle inflammation is not fully understood. We hypothesized that exercise training would inhibit skeletal muscle inflammation and alter macrophage infiltration into muscle independently of weight loss. Wild type C57BL/6 male mice were fed a chow diet or a high‐fat diet (HFD, 45% calories fat) for 6 weeks. Then, mice maintained on the HFD either remained sedentary (HFD Sed) or exercised (HFD Ex) on a treadmill for another 6 weeks. The exercise training protocol involved conducting intervals of 2 min in duration followed by 2 min of rest for 60 min thrice weekly. Chow‐fed control mice remained sedentary for the entire 12 weeks. Muscle cytokine and macrophage gene expression analysis were conducted using qRT‐PCR, and muscle macrophage content was also measured using immunohistochemistry. Muscle cytokine protein content was quantified using a cytokine array. The HFD increased adiposity and weight gain compared to chow‐fed controls. HFD Sed and HFD Ex mice had similar body mass as well as total and visceral adiposity. However, despite similar adiposity, exercise reduced inflammation and muscle macrophage infiltration. We conclude that Endurance exercise training modulates the immune‐metabolic crosstalk in obesity independently of weight loss, and may have potential benefits in reducing obesity‐related muscle inflammation.